Analisis Pengaruh Karakteristik Perusahaan terhadap Kebijakan Dividen pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Serly Serly; Fanny Desmita Liyanti (Faculty of Economics, Universitas Internasional Batam, 2021)
Dividend payout ratio is an important thing in the company. Investors can use the dividend payout ratio as a basis for making investment decisions. The purpose of this study is to examine whether the impact of firm size, leverage, profitability, firm age, growth, cash holding, and cash flow volatility on dividend payout ratio on the firms listed in Indonesia Stock Exchange (IDX) from 2015 to 2019. The sample of this study consist of 460 firms from 688 firms listed in IDX from 2015 to 2019. The sampling method in this study was purposive sampling. The total sample is 2,300 observational data and 151 outlier data, after reducing the outlier data, the observational data becomes 2,149 data. The results of this study show that company age has a significant positive impact on the dividend payout ratio, while company size, leverage, profitability, growth, cash holdings and cash flow fluctuations have no effect on the dividend payout ratio. The results of the regression model test show that the ability of all independent variables can explain 62.318% of the dividend policy, while 37,682% is explained by other variables not included in the research model.